Islamic Education And The Challenges Of Globalization - Suardi; Bahaking Rama; Afifuddin Harisah (Yayasan Azhar Amanaa Yogyakarta, 2026)
Globalization has brought significant changes to various aspects of human life, including the field of education. The advancement of information technology, communication, economics, and global culture presents both opportunities and challenges for Islamic education. On the one hand, globalization provides broader access to knowledge and technology; on the other hand, it may give rise to various issues such as moral degradation, identity crises, secularization, and the weakening of Islamic values among younger generations. This article aims to examine the challenges posed by globalization to Islamic education and to explore strategies for addressing them. The study employs a library research method by analyzing relevant literature, books, and scholarly articles. The findings indicate that Islamic education needs to undergo transformation through the integration of religious and scientific knowledge, the strengthening of character education, the development of digital literacy, the enhancement of educators’ competencies, and the productive and ethical utilization of technology. Therefore, Islamic education can remain relevant in responding to global dynamics while preserving its identity and fundamental Islamic values.